2-D numerical study of hydrated wedge dynamics from subduction to post-collisional phases. Issue 2 (3rd August 2017) - Regorda, Alessandro; Roda, Manuel; Marotta, Anna Maria; Spalla, Maria Iole
Abstract: We developed a 2-D finite element model to investigate the effect of shear heating and mantle hydration on the dynamics of the mantle wedge area. The model considers an initial phase of active oceanic subduction, which is followed by a post-collisional phase characterized by pure gravitational evolution. To investigate the impact of the subduction velocity on the thermomechanics of the system, three models with different velocities prescribed during the initial subduction phase were implemented. Shear heating and mantle hydration were then systematically added into the models. We then analysed the evolution of the hydrated area during both the subduction and post-collisional phases, and examined the difference in P max – T (maximum pressure–temperature) and P – T max (pressure–maximum temperature) conditions for the models with mantle hydration. The dynamics that allow for the recycling and exhumation of subducted material in the wedge area are strictly correlated with the thermal state at the external boundaries of the mantle wedge, and the size of the hydrated area depends on the subduction velocity when mantle hydration and shear heating are considered simultaneously. During the post-collisional phase, the hydrated portion of the mantle wedge increases in models with high subduction velocities. The predicted P – T configuration indicates that contrasting P – T conditions, such as Barrovian- to Franciscan-type metamorphic gradients, can contemporaneously characterize different portions of the subduction system during both the active oceanic subduction and post-collisional phases and are not indicative of collisional or subduction phases.